Literature Study: SETS-Based Learning Videos to Improve Student Learning Outcomes - Annas Setyawan, Pramudya; Priyanto, Wawan; Kartinah, Kartinah (Jurnal Gentala Pendidikan Dasar, 2022)
The learning process and learning outcomes are both important and closely related in learning. This study aims to examine the implementation of science learning assisted by SETS-based learning videos to improve student learning outcomes. This research is a qualitative research conducted using a literature study. Data collection was carried out by reviewing several articles that matched the title of the research article. SETS-based learning videos focus on real problems that have science and technology components from the student’s point of view which have concepts and learning processes. Learning is expected to be able to make students better understand the material presented through learning videos. Good student understanding makes student learning outcomes increase. The results of this study were SETS-based learning videos could improve high grade students’ learning outcomes. Supporting literature states that SETS-based learning videos can improve student learning outcomes. The implementation of SETS-based learning videos can be used in online and offline learning.